Corrupted Book 3 - Scottoline, Lisa (New York : St. Martins Press, 2015)
Taking the case of a former classmate who has been wrongly accused of murdering a bully who sent him to juvenile detention when they were children, Bennie is forced to relive some of the darkest memories of her life in order to defend the boy she once failed.
Keywords: Women lawyers -- Fiction; Murder -- Investigation; Fiction